Karen N. Scott and David L. VanderZwaag (eds.) Research Handbook on Polar Law (Cheltenham/Northampton: E. Elgar, 2020) - Sara Fusco (Nordicum-Mediterraneum, 2022)
The Research Handbook on Polar Law by Edward Elgar Publishing is part of the series of Research Handbooks that the British publishing house offers as a research focus in different disciplines and properly indexed in particular themes. In the case of the Research Handbook in Polar Law, the collection of 22 articles attempts to offer a comprehensive view of what constitutes the dimension of Polar Law: biodiversity, culture, politics.